A comparison of obstetrical outcomes and costs between misoprostol and dinoprostone for induction of labor. (16th November 2016) - Nadia Bennett, Kunzier; Park, Hyein; Cioffi, Joseph; Calixte, Rose; Vintzileos, Anthony
Abstract: Objective : The objective of this study is to compare resource utilization (efficiency) and obstetrical/cost outcomes of single dose misoprostol versus dinoprostone for induction of labor (IOL) at term. Methods : Retrospective cohort of induced deliveries 37–41 weeks gestation presenting with a Bishop score ≤4 using single-dose-50 mcg vaginal misoprostol or 10 mg-dinoprostone vaginal-inserts. Dinoprostone patients were compared (5:1) with misoprostol patients. The primary outcome variable was length of L&D stay (proxy for resource utilization). Baseline characteristics, clinical outcomes, and costs were compared. Results : Three-hundred thirty-one patients were included, 276 received dinoprostone and 55 received misoprostol. The misoprostol group had statistically significant decreased time to active labor [median 8 h (1.6, 24) versus 12(0.8, 52)], time-to-delivery [median 11 h (4, 31) versus 17(2.8, 56)] and L&D stay [median 16 h (13, 28) versus 24(18, 30)]. Differences remained significant after adjustment for race, method of delivery, birth weight, gravidity/parity, gestational age, and BMI (adjusted p values <0.001, <0.01, and < 0.05, respectively). There were no statistical differences in Apgar scores, tachysystole rate, cesarean section rate, and composite maternal/neonatal morbidity. A policy of using misoprostol would result in annual cost savings of approximately 242 500 at our institution as compared with dinoprostone. Conclusion : Single-dose misoprostol is more efficient in IOL at term with respect to L&D utilization and cost and its use is not associated with increased adverse obstetrical outcomes.